Piling test / Muhammad Zikry Mohd Sabri - Mohd Sabri, Muhammad Zikry (Universiti Teknologi MARA, Perak, 2021)
The technique and planning, as well as the equipment and materials used in the piling test, are briefly described in this report. Engineers, site supervisors, and skilled labourers are all involved in the piling test process. The types of equipment utilised during the piling operation are briefly described in this paper. Several issues arose during the procedure, and they were all identified. This study also includes some recommendations for resolving the issues that occurred.